2007
DOI: 10.1080/14767050701511650
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum concentrations of the chemokine CXCL10/IP-10 are elevated in acute pyelonephritis during pregnancy

Abstract: Pyelonephritis in pregnant women is associated with an increased maternal serum concentration of the chemokine CXCL10/IP-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…Activation of the innate limb of the immune response is thought to protect mother and fetus against infection [118]. Infection during pregnancy is known to lead to an exaggerated systemic intravascular inflammatory response with increased concentrations of cytokines [118, 133, 134]. This occurs in the context of both bacterial and viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the innate limb of the immune response is thought to protect mother and fetus against infection [118]. Infection during pregnancy is known to lead to an exaggerated systemic intravascular inflammatory response with increased concentrations of cytokines [118, 133, 134]. This occurs in the context of both bacterial and viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings herein are different, as we observed that the median plasma endocan concentration was lower in pregnancies complicated by acute pyelonephritis than in non-pregnant patients. This is a puzzling observation, given that our systematic studies of the behavior of cytokines [230], chemokines [231], complement [232,233] in acute pyelonephritis and preeclampsia suggest that both conditions are associated with a pro-inflammatory state. However, studies of the transcriptome of peripheral blood in patients with preeclampsia [234] and pyelonephritis [235] suggest that the molecular details of the inflammatory response differ.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the median maternal serum concentrations of IL-8, TNF-α, IL-6, IL-7, IL-10, and interferon (IFN)-γ were higher in pregnant women with acute pyelonephritis than in gestational age-matched normal pregnant women [19]. Moreover, acute pyelonephritis in pregnancy was found to be associated with higher median maternal serum concentrations of the pro-inflammatory chemokine CXCL-10 (also known as IP-10) [41] and higher median maternal plasma concentrations of the pro-inflammatory adipokine resistin [72] than in normal pregnant women. Resistin concentrations are considered an index of the severity of sepsis and a prognostic factor for survival in critically ill nonpregnant patients [55, 72, 122].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this increased susceptibility to microbial products remain unknown. However, acute pyelonephritis during pregnancy has been associated with changes in maternal blood concentrations of soluble cluster of differentiation (CD) 30 (an index of Th2 immune response) [61], adipocytokines (retinol binding protein-4 [141], adiponectin [70], visfatin [71], and resistin [72]), T-cell chemokines (C-X-C motif chemokine 10, CXCL-10) [41], complement products (C5a [117]and fragment Bb [118]), protein Z [92], and soluble tumor necrosis factor-related apoptosis inducing ligand (TRAIL) [18]. …”
Section: Introductionmentioning
confidence: 99%